2021
DOI: 10.3366/ijhac.2021.0264
|View full text |Cite
|
Sign up to set email alerts
|

From Disparate Disciplines to Unity in Diversity: How the PARTHENOS Project Has Brought European Humanities Research Infrastructures Together

Abstract: Since the first ESFRI roadmap in 2006, multiple humanities Research Infrastructures (RIs) have been set up all over the European continent, supporting archaeologists (ARIADNE), linguists (CLARIN-ERIC), Holocaust researchers (EHRI), cultural heritage specialists (IPERION-CH) and others. These examples only scratch the surface of the breadth of research communities that have benefited from close cooperation in the European Research Area. While each field developed discipline-specific services over the years, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Oleh karena itu siswa membutuhkan penjelasan yang baik dari guru dan gambaran yang nyata agar siswa mampu menguasai materi dengan baik. Materi Bhinneka Tunggal Ika ini membutuhkan pembelajaran yang tidak hanya melalui teori yang ada di buku pegangan saja, tetapi memerlukan media pembelajaran yang menarik dan memudahkan siswa dalam memahami materi (Bazzi, 2019;Fedosov, 2021;Kuppens, 2020;Liu, 2019;Uiterwaal, 2021).…”
Section: Pendahuluanunclassified
“…Oleh karena itu siswa membutuhkan penjelasan yang baik dari guru dan gambaran yang nyata agar siswa mampu menguasai materi dengan baik. Materi Bhinneka Tunggal Ika ini membutuhkan pembelajaran yang tidak hanya melalui teori yang ada di buku pegangan saja, tetapi memerlukan media pembelajaran yang menarik dan memudahkan siswa dalam memahami materi (Bazzi, 2019;Fedosov, 2021;Kuppens, 2020;Liu, 2019;Uiterwaal, 2021).…”
Section: Pendahuluanunclassified
“…Archaeological data survival and availability has since become an acknowledged research objective, and several transnational projects have been commenced in order to coordinate and integrate relevant efforts by individual researchers and existing policies by institutions or national bodies, such as ARIADNE and ARIADNEplus (https://ariadne-infrastructure. eu/, accessed on 10 October 2022) [28], PARTHENOS (https://www.parthenos-project.eu/, accessed on 10 October 2022) [29] and SEADDA (https://www.seadda.eu/, accessed on 10 October 2022) [30]. Recently, the preservation of software code has also received attention, as it is considered to increase methodological transparency, computational reproducibility, and the verifiability of research results [31,32].…”
Section: Studying Digital Legaciesmentioning
confidence: 99%
“…Of course, these principles consider many technical aspects, requiring considerable effort in their application and underscoring the need for formal training, see also [35] (pp. [27][28][29][30][31]. Furthermore, the results of the on-going ERCfunded project CAPTURE indicated that the lack of interoperability of archaeological data and information may be the outcome of techno-politics.…”
Section: Studying Digital Legaciesmentioning
confidence: 99%